1998
DOI: 10.1183/09031936.98.12020374
|View full text |Cite
|
Sign up to set email alerts
|

The haemodynamic response to exercise in chronic obstructive pulmonary disease: assessment by impedance cardiography

Abstract: This study aimed to determine the differences in haemodynamic responses to a standard incremental exercise test between outpatients with chronic obstructive pulmonary disease (COPD) and age-matched controls and to discover the relationship between severity of airflow obstruction and exercise haemodynamics in COPD. Twenty-two male patients with COPD (forced expiratory volume in one second (FEV1)/vital capacity (VC))<80% predicted) and 20 age-matched male controls performed an incremental exercise test (10 W … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…During exercise there was a rapid increase in Ppa even in patients with normal resting pressures. The findings of a reduced SV response during exercise together with an increase in Ppa are consistent with those of previous studies [3,5,21] and fit with the idea that this reduced SV during exercise is caused by an increased afterload.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…During exercise there was a rapid increase in Ppa even in patients with normal resting pressures. The findings of a reduced SV response during exercise together with an increase in Ppa are consistent with those of previous studies [3,5,21] and fit with the idea that this reduced SV during exercise is caused by an increased afterload.…”
Section: Discussionsupporting
confidence: 81%
“…KEYWORDS: Chronic obstructive pulmonary disease, magnetic resonance imaging, pulmonary hypertension, sildenafil, stroke volume S everal studies have shown that stroke volume (SV) in chronic obstructive pulmonary disease (COPD) patients may be reduced at rest and frequently fails to increase during exercise [1][2][3][4][5]. Since cardiac output is proportionally related to tissue oxygen delivery, impaired SV response (when not compensated by an increased cardiac frequency) may contribute to reduced exercise capacity in COPD.…”
mentioning
confidence: 99%
“…Decreases in exercise cardiac output have been documented (Stewart and Lewis 1986;Bogaard et al 1998). There is a decrease in right ventricular ejection fraction (Morrison et al 1987) which fails to increase with increases in exercise workload and right ventricular end-diastolic volume (Mahler et al 1984;Uenami et al 1986).…”
Section: Relevance To Copdmentioning
confidence: 97%
“…There appears to be considerable variability between patients. Stewart and Lewis [42]and Bogaard et al [43]both found a decrease in cardiac output during exercise in some patients with COPD and suggested that severity of expiratory flow limitation might be an important determinant of exercise cardiac output. Morrison et al [44]found strong correlations between maximal exercise oxygen consumption in COPD on the one hand and right ventricular ejection fraction, exercise stroke volume, and exercise cardiac output on the other.…”
Section: Cardiovascular Factors Limiting Exercise In Copdmentioning
confidence: 99%
“…Just as there is variability in exercise performance and exercise cardiac output among patients with COPD [42, 43], not all patients with COPD have a detectable anaerobic threshold [50, 51, 52]. Perhaps these are patients who have a true ventilatory limit to exercise.…”
Section: The Competition Between Ventilatory and Skeletal Musclesmentioning
confidence: 99%